Feature Model for Pet Health Application Domain using Feature Oriented Domain Analysis - Satoh, Ajeng Nurhidayati A Darsan; Budiardjo, Eko K.; Mahatma, Kodrat (The Indonesian Journal of Computer Science, 2024)
According to a survey of Indonesian pet healthcare service users, only 19% of pet health applications are used since the functions offered by the applications are insufficient to meet the needs of the users. Developing feature model for the pet health application domain is the goal of this research. Using a mixed-methods approach, this research examined nine pet health apps which are available on Google Play and the App Store, observed 30 pet health service consumers through surveys using purposive sampling, and conducted document analyses. The Feature Oriented Domain Analysis (FODA) approach is applied within the Software Product Line Engineering (SPLE) framework. The result of this research is a pet health application domain feature model consisting of five non-functional requirements and 45 functional requirements. With an average assessment score of 96%, domain experts have determined that the feature model implementation in this study is in line with user needs.